Effect of intensity and frequency of various training schedules on running performance - Richardson, Ronald (My University, 1967)
The purpose of this study was to determine the effect of frequency and intensity of various training schedules on running performance. The distance in feet that the subjects were able to run in one minute was considered to be his running performance for this study. The intensity of the training schedules were determined by one of the following interval methods. The methods used were twelve repetitions of fifteen seconds; six repetitions of thirty seconds; four repetitions of forty-five seconds; three repetitions of sixty seconds; two repetitions of ninety seconds; and one workout consisting of one thirty second run, one sixty second run, and one ninety second run. The frequency of the training schedules were either five days per week or three days per week with the workouts on alternate days. The investigator used 280 male sophomore physical education students presently attending William Horlick High School of Racine, Wisconsin, for the subjects of this investigation. Twelve groups of twenty students each participated in the experimental training program. Six of these were assigned to the five day per week training schedules and six were assigned to the three day per week schedule. In addition to twelve experimental groups two groups were assigned to be control groups with one each assigned to the different frequency levels. The students were assigned to each of the groups by random selection which consisted of drawing their names out of a hat. Each of the groups consisted of students having physical education at various times during the day so that the time in which the training schedule was followed would not influence the results. The twelve experimental groups were tested at the end of each week. The test consisted of a one minute run in which they were instructed to run as far as they could in the one minute time limit. Their distance was recorded to the nearest foot. The two control groups were measured in the same way with the exception that they were measured only at the beginning and again at the conclusion of the study. The control groups participated in a gymnastic unit with no training other than class work. The twelve training schedule groups involved in the study were varied as to frequency and intensity of training schedules. Due to the small size of each group the statistical design used to analyze the outcomes of this study was a computerized small sample t-test. Through the use of a computer it was relatively easy to analyze all combinations throughout the groups. The results of the investigation were: 1. All of the training groups have a statistically significant mean gain over their initial measurement. Five of the five day per week training groups has a statistically significant mean gain over their initial measurement. Five of the five day per week training groups has a statistically significant mean gain of over 40 feet, two of the three day per week groups had a statistically significant mean gain of over 30 feet. All of these measurements were significant at the 0.05 level of significance. 2. There was a significant difference at the 0.05 level of significance between the mean gains between the two control groups and nine of the experimental groups. The experimental groups I, VII and IX did not display this difference at the 0.05 level of significance. 3. There was no difference at the 0.05 level of significance between the mean gains of the twelve experimental groups. Based on the results of this investigation the following conclusions appear to be justified: 1. Running performances can be improved during the first six weeks of training as well by a three day per week practice schedule, as by a five day per week practice schedule. 2. Improvement in running performance for the three day per week training groups seems to be slower than those following a five day per week plan, but they do seem to show more consistency in their performances than do the five day per week groups. 3. During the first six weeks of a training program there is no significant difference between the mean gains at the 0.05 level of significance among the various levels of intensity used in the study.
Keywords: Running -- Training; Running -- Physiological aspects